Self-Assessment of Problem-Solving Skills and Clinical Reasoning Among Sixth-Year Medical Students In Baghdad University / College of Medicine - Ahmed Moaffak; Ibraheem Nashwan Abbas; Ahmed Abbas Abdulrazaq; Ali Mohammed Jawad Almothafar (Universidad de Murcia, 2023)
Abstract. Objectives: To assess the level of problem solving skills of Sixth grade medical students of College of Medicine/ University of Baghdad using self-assessment tool. Materials and Methods: A cross-sectional study to assess Problem Solving Disposition in Sixth year Medical Students in College of Medicine/ University of Baghdad. A printed survey of the questionnaire was distributed to sixth year medical students in august 2022. A sample of 151 students participated in the study by filling of the printed questionnaire which was validated by a previous study in a medical school in Mexico. Results: The number of sixth Grade medical students in University of Baghdad/ College of medicine that participated in the study was 151 of whom 70 (46.35 %) were males and 81 (53.65 %) were females. The mean score of the "knowledge of discipline" was 2.973± 0.999, as for the "pattern recognition" component the mean was 2.198 ±0.559 , and the mean for the "application of general strategies" component was 2.158± 0.492. The independent sample T-test results for the "Knowledge of discipline" category showed a mean score for females of 3.137 and a mean score for males of 2.778 with a p value >0.05. For correlations between the categories one of the items of the "Pattern Recognition" category had a positive correlation with a statistical  significance with 2 items from "Application of general strategies for problem solving" category. Conclusion: Sixth year medical students in University of Baghdad/ college of medicine are better  self-perceived in the pattern recognition and application of general strategies for problem-solving categories than the knowledge of discipline, males assess themselves in remembering concepts as better than their female counterparts, students who rate themselves higher as being able to identify the pattern of a problem also rate themselves fairly when it comes to applying what they learnt in dealing with it. Further studies with larger sample size are needed to evaluate the entirety of students from different stages and correlate with their progress throughout their education.